Evaluation of the temperature of the rotary dryer with LPG fuel in drying cherry coffee - Alit, I.B.; Susana, I.G.B.; Adhi, I.G.A.K.C.; Mulyanto, A. (Universitas Mataram, 2025)
Utilization of rotary dryers with liquefied petroleum gas (LPG) energy sources as an alternative to solar drying, which is highly dependent on the weather. This dryer is applied to small farmers to dry cherry coffee. The results of the study showed that the drying temperature reached an average of 63.92oC to dry a sample of 10 kg of cherry coffee. From testing, this sample still produced a reasonably high outlet temperature of the drying chamber, which was an average of 62.07oC. From this condition, it is possible to increase the amount of cherry coffee to be dried, and further testing is needed. LPG-based rotary dryers are very easy for small farmers. The drying process can be carried out all the time because it does not depend on the weather. In addition, LPG in Indonesia for small farmers is still subsidized, so it is economically affordable. The shorter drying time than solar drying allows small farmers to carry out their production process sustainably. In 20 hours of testing, it was able to reduce the moisture content from 62.84% to 9.95%.